1996
DOI: 10.1055/s-0038-1650623
|View full text |Cite
|
Sign up to set email alerts
|

Plasmin Is a Specific Stimulus of the 5-Lipoxygenase Pathway of Human Peripheral Monocytes

Abstract: SummaryThe objective of this study was to characterize the plasmin-induced stimulation of leukotriene (LT) B4 biosynthesis in human peripheral monocytes (PM). Plasmin up to 175 × 10-3 CTA U/ml triggers a concentration-dependent release of 5-lipoxygenase-derived LTB4 while release of the cyclooxygenase products thromboxane (TX) B2 and prostaglandin (PG) E2 remained unaffected. The stimulatory effect appeared to be specific in as much as 1) it was found in PM, but not in polymorphonuclear neutrophils (PMN), 2) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…Plasmin(ogen) is not essential for inflammatory cell migration, but it seems to play a critical role in normal functioning, especially bacterial clearance and necrotic tissue removal. In vitro studies have shown that plasmin is a potent and selective stimulus for human peripheral monocytes (33,34). For instance, plasmin has been shown to release macrophage-derived IL-1 and to activate transforming growth factor ␤ (35).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmin(ogen) is not essential for inflammatory cell migration, but it seems to play a critical role in normal functioning, especially bacterial clearance and necrotic tissue removal. In vitro studies have shown that plasmin is a potent and selective stimulus for human peripheral monocytes (33,34). For instance, plasmin has been shown to release macrophage-derived IL-1 and to activate transforming growth factor ␤ (35).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that 5-LOX is overexpressed in the skin of patients with SSc compared with the skin of normal controls, and that skin fibroblasts from patients with SSc generate more LTB 4 than do those from normal subjects (37). There are also several hypothetical stimuli that have been shown to contribute to the pathogenesis of SSc and might be responsible for 5-LOX stimulation in vivo, including transforming growth factor ␤ and the coagulation/fibrinolysis cascade (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Pla is able to activate monocytes and trigger the release of lipid mediators, cytokines, and chemokines in vitro (16,18,19). Owing to the importance of cytokines and chemokines to cell migration, we investigated pleural levels of the cytokines IL-1b, IL-6, and TNF-a and the chemokines MCP-1 (CCL2), KC/CXCL1, and MIP-2 (CXCL2) during Pla-induced mononuclear traffic into the pleural cavity.…”
Section: Serine Protease Activity and Lbs Are Required For Pla-inducementioning
confidence: 99%
“…Plasmin stimulates expression of cytokines (TNF-a, IL-6, IL-1a/b, CD40), chemokines (MCP-1/CCL2), tissue factors, and the release of lipid mediators and chemotaxis in purified monocytes (16)(17)(18)(19). Some of these effects are followed by the activation of the transcription factors NF-kB and AP-1 (16)(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation